2021
DOI: 10.1182/blood-2021-149582
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Complete Remission and Survival in Acute Myeloid Leukemia Using Supervised Machine Learning

Abstract: Achievement of complete remission (CR) signifies a crucial milestone in the therapy of acute myeloid leukemia (AML) while refractory disease is associated with dismal outcomes. Hence, accurately identifying patients at risk is essential to tailor treatment concepts individually to disease biology. Machine Learning (ML) is a branch of computer science that can process large data sets for a plethora of purposes. The underlying mechanism does not necessarily begin with a manually drafted hypothesis model. Rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The results of our study are consistent with the studies by Eckardt et al[ 28 ], Coombes et al [ 41 ], and Orgueira et al [ 14 ] In these studies, after implementing various ML models to predict the survival of patients with leukemia, the SVM classifier yielded the best performance. In a study by Karami et al, the SVM had better performance with 85.17% accuracy and 0.93% AUC for the survival prognosis of AML patients [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of our study are consistent with the studies by Eckardt et al[ 28 ], Coombes et al [ 41 ], and Orgueira et al [ 14 ] In these studies, after implementing various ML models to predict the survival of patients with leukemia, the SVM classifier yielded the best performance. In a study by Karami et al, the SVM had better performance with 85.17% accuracy and 0.93% AUC for the survival prognosis of AML patients [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that numerous clinical and non-clinical predictors influence CML survival. In reviewed studies, after performing feature selection, a number of demographical and clinical manifestation variables such as age [ 27 , 31 , 39 , 40 ], sex [ 14 , 27 , 40 ], body mass index (BMI) [ 10 , 27 , 30 , 31 ], race [ 27 , 40 ], body pain [ 14 , 25 , 27 , 28 , 40 , 41 ], general malaise [ 10 , 14 , 27 , 31 , 40 ], fever [ 10 , 26 , 28 30 ], night sweats [ 25 , 28 30 , 41 ], unexplained hemorrhage [ 10 , 26 , 28 , 30 , 39 ], general infection [ 14 , 31 , 40 ], enlarged spleen [ 10 , 14 , 27 , 31 , 39 , 40 ], cachexia [ 25 , 27 , 30 , 31 ], anorexia [ 10 , 14 , 29 , 31 ], and drug resistance [ 25 , 27 – 29 , 41 ] are determined as the most important predictors affecting CML survival. Besides, neutrophil/lymphocyte count [ 10 , 14 , 25 – 27 , 29 , 31 , 39 ], lactate dehydrogenase (LDH)...…”
Section: Discussionmentioning
confidence: 99%
“…These limitations stem from the reuse of the same subjects, contrasting with the synthesis of new data in approaches like VAEs (or other generative AI algorithms). Moreover, AI-synthetic data have already been used to mimic clinical trials in patients with leukemia and other healthcare applications [50][51][52][53][54]. Notably, tech giants like Amazon (for Alexa) and Google (for self-driving cars), as well as pharmaceutical companies like Roche, utilize synthetic data to train their systems.…”
Section: Discussionmentioning
confidence: 99%
“…This application process often incorporates various algorithm optimizations to achieve high accuracy. Classification, one of the data mining methods for predicting specific classes [21], [22], has proven effective in the early detection and accurate diagnosis of disease including glaucoma [23], [24], brain tumors [25]- [27], acute lymphoblastic leukemia [28], [29], and PD [30], [31].…”
Section: Introductionmentioning
confidence: 99%